Development Trajectories : An Evolutionary Approach to Integrating Governance and Growth - Levy, Brian (World Bank, Washington, DC, 2012)
This note introduces an evolutionary approach to economic and governance reform. It lays out two especially prevalent trajectories that differ starkly from one another in how they prioritize and sequence economic growth, state building, and the development of civil society and political institutions. The first trajectory focuses initially on investments in state capacity. The second initially prioritizes smaller, more catalytic entry points and addresses specific capacity and institutional constraints as and when they become binding. Over the longer term, both trajectories endogenously generate incentives to strengthen institutions that underpin economic competition and political accountability. But over the short to medium term, the strengths of one trajectory are mirrored as the weakness of the other. For many low-income countries, the combination of rapid growth plus a seeming excess of either order or chaos may thus be in the (medium-term) nature of things, rather than an aberration that requires fixing.